THE FEMALE ATHLETE TRIAD IN GYMNASTICS - Theofanis Siatras; Dimitra Mameletzi (Science of Gymnastics Journal)
The female athlete triad consists of three interrelated components: low energy availability (with or without eating disorders), amenorrhea and osteoporosis. Female gymnastics is a sport characterized by regular exposure to high-impact prolonged physical training at an early age, requiring strict control of energy consumption. Could this lead to the female athlete triad? The bibliographic data bases of PubMed, Scopus and ScienceDirect were used to identify relevant articles, using appropriate key words as Athletic triad, Eating disorders, Amenorrhea, Osteoporosis, Bone mineral density, Bone mass, Gymnastics and Adolescent. One hundred and thirty six papers were selected and their review was mainly focused on the occurrence of eating disorders, amenorrhea and osteoporosis in female gymnasts. The bibliography revealed that in gymnastics, each component of the female athlete triad alone or a combination of them may occur. It was concluded that, even though the mechanical loading on the female gymnast’s skeleton has a site-specific beneficial effect on bone mineral density, it cannot offset the detrimental effect of hormonal deficiency on the skeleton caused by chronic energy deficiency. Low energy availability (with or without eating disorders), menstrual disorders and premature osteoporosis may lead to decreased athletic performance and adverse long-term health consequences. A concerted effort among coaches, athletic trainers, parents, athletes, and healthcare personnel is optimal for the prevention, early diagnosis and treatment of the female gymnasts’ athlete triad to preserve their health.